Climate Risk Disclosure in Mining: Transparency and Corporate Accountability - Hartono, Rudi; Kamakaula, Yohanes (MSJ : Majority Science Journal, 2026)
The mining industry is both a major contributor to climate change and highly exposed to climate-related risks, making climate risk disclosure (CRD) a critical tool for enhancing corporate transparency and accountability. However, despite increasing reporting practices, the quality and consistency of climate disclosures remain uneven. This study aims to analyze how CRD contributes to transparency and accountability in the mining sector. The research employs a qualitative approach using a systematic literature review and document analysis of relevant academic studies and reporting frameworks such as TCFD and GRI. Data were collected through structured stages of identification, screening, eligibility, and inclusion, and analyzed using thematic and content analysis. The findings indicate that while climate disclosures are increasingly adopted, many remain symbolic and lack integration with financial impacts and strategic decision-making. High-quality disclosures—characterized by comprehensive emission reporting, governance involvement, and adherence to international standards—enhance transparency and accountability. However, challenges such as greenwashing, inconsistent standards, and weak market responses persist. In conclusion, climate risk disclosure has significant potential to strengthen transparency and accountability in the mining industry, but its effectiveness depends on the depth, consistency, and substantive integration of disclosed information.